PEMANFAATAN MEDIA UNPLUGGED UNTUK MENINGKATKAN PEMAHAMAN KONSEP KOMPUTASIONAL SISWA KELAS VI SDN BANGKOK BOYOLALI - Ristiya Krisnawati; Robith Khoiril Umam (Yayasan Pendidikan Literasi Borneo, 2025)
This study aims to describe the process and outcomes of implementing unplugged learning media to improve sixth-grade students’ understanding of computational concepts at SDN Bangkok Boyolali, an elementary school with limited internet access and technological resources. Unplugged media refer to a computational learning approach conducted without digital devices, emphasizing concrete activities, educational games, logical problem-solving, and collaborative engagement. The research employed a Classroom Action Research (CAR) method using the STAR framework (Situation, Task, Action, Result). The Situation stage identified the initial learning conditions showing low computational understanding due to technological constraints. The Task stage focused on developing unplugged media suitable for students’ characteristics, while the Action stage involved implementing logic-based games and collaborative learning activities. The Result stage emphasized the analysis of learning improvement and behavioral changes. The subjects consisted of 22 sixth-grade students during the first semester of the 2025/2026 academic year. Data were collected through observation, conceptual understanding tests, and interviews, then analyzed descriptively using qualitative and quantitative approaches. The findings revealed a significant increase in the average score of students’ computational concept understanding, from 67.3 in the pre-cycle to 79.6 in the first cycle and 88.1 in the second cycle. Furthermore, students demonstrated higher enthusiasm, collaboration, and the ability to explain their reasoning systematically. It can be concluded that implementing unplugged media within the STAR framework effectively enhances students’ computational thinking skills in elementary schools with limited technology and serves as a contextual learning alternative to support 21st-century skills.